(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
The present work deals with the simulation of electronic transport through a single dimensional carbon atoms chain device coupled to Graphene nanoribbons (GNR) electrodes. In order to observe electron transport in a more specific manner, applied voltage is regulated across an eight atoms long carbon chain resistor sandwiched between two identical semi-infinite semiconducting Armchair Graphene nanoribbon (AGNR) electrodes. The entire device is 2.06nm in length consisting of a 0.93nm long monoatomic carbon chain with eight carbon atoms coupled with two 1.13nm wide 7-AGNR electrodes. Nonequilibrium green’s function (NEGF) technique coupled with density functional theory (DFT) generally used to simulate electronic transport in such systems is employed. The experimental realization of stable carbon chain and 7-AGNR observed in past studies motivated us to link these two experimentally obtained carbon based materials and construct a device in order to investigate electron transport properties theoretically. Meanwhile, the continuous advancement in nanotechnology realization of such devices experimentally may be anticipated in near future, with which the authenticity of the present and other similar reported simulated results may be validated. In this device the current is calculated as a function of potential difference within the 0.0-2.5V range. The I-V curve exhibits a nonconducting region upto 0.81V, followed by steep rise in current magnitude to a maximum value 13.0 ¹A as in semiconductor diodes, involving non-linear characteristic curve displaying a sharp negative differential resistance (NDR) pattern, which is the main focus of our study. Nano devices displaying such unusual I/V characteristics have been considered for developing application oriented futuristic miniaturized devices.